2010
DOI: 10.1088/0029-5515/50/6/064010
|View full text |Cite
|
Sign up to set email alerts
|

Overview of L–H power threshold studies in NSTX

Abstract: A summary of results from recent L–H power threshold (P LH) experiments in the National Spherical Torus Experiment is presented. First P LH (normalized linearly by plasma density) was found to be a minimum in double-null configuration, tending to increase as the plasma was shifted more strongly towards lower- or upper-single null configuration with either neutral beam or rf heating. The measured P LH/n e was comparable with neutral beam or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…Note that, in this study, the definition of divertor configuration in terms of small dR sep seems somewhat arbitrary and the presence of a second X-point inside the vacuum vessel and close to the plasma might affect on the edge plasma, wall interaction as well as recycling, which may result in the distinctive findings on EAST. On the other hand, similar results from ASDEX-Upgrade and MAST [19] and studies on NSTX [20] showed a minimum P thr also near balanced DN configuration. These findings show that the occurrence of a minimum in P thr is a universal feature in EAST, regardless of wall materials, pointing to a potential role played by SOL and divertor physics in the L-H transition.…”
Section: Summary and Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Note that, in this study, the definition of divertor configuration in terms of small dR sep seems somewhat arbitrary and the presence of a second X-point inside the vacuum vessel and close to the plasma might affect on the edge plasma, wall interaction as well as recycling, which may result in the distinctive findings on EAST. On the other hand, similar results from ASDEX-Upgrade and MAST [19] and studies on NSTX [20] showed a minimum P thr also near balanced DN configuration. These findings show that the occurrence of a minimum in P thr is a universal feature in EAST, regardless of wall materials, pointing to a potential role played by SOL and divertor physics in the L-H transition.…”
Section: Summary and Discussionsupporting
confidence: 72%
“…This observation has been confirmed in a series of dedicated experiments (B × ∇B ↓) conducted in 2012 [7,14]. This is in contrast to other tokamaks [15][16][17][18][19][20]. In addition, all the type-I ELMy H-modes were obtained in the LSN configuration (B × ∇B ↑) in the 2012 campaign, suggesting that LSN with the ion ∇B drift away from the major X-point appears to facilitate achievement of highperformance stable H-mode plasmas on EAST.…”
Section: L-h Power Threshold and Divertor Configuration Effectsmentioning
confidence: 56%
See 2 more Smart Citations
“…Two lithium evaporators deposit lithium vapor on the vessel floor; this lithium primarily coats the divertor, and to a lesser extent, the center column and lower passive plates [83,84]. This conditioning has many beneficial effects, including the elimination of ELMs [85], reduction of electron transport [86] and the lowering of the H--mode threshold [87]. The elimination of ELMs, however, typically leads to an uncontrolled accumulation of impurities [84], including metals and carbon from the plasma facing components.…”
mentioning
confidence: 99%